Nasal rhinosporidiosis in a mule - Berrocal, Alexis (2007)
A mass was removed from the nostril of a mule that exhibited unilateral epistaxis and nasal discharge. Impression smears revealed oval structures consistent with spores of Rhinosporidium seeberi. Microscopically, the mass was composed of fibrovascular granulomatous tissue containing sporangia R. seeberi. Surgical excision and antifungal treatment proved curative.